Prostatic lesions: Histopathological study in a tertiary care hospital - Bhatta, S.; Hirachan, S. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Prostatic lesions like Nodular hyperplasia of prostate, inflammation and carcinoma are common causes of morbidity and mortality in males. The incidence of these lesions increases with age. This study was conducted with the objective of evaluating histopathological pattern of prostatic lesions.Methods: This was a retrospective study conducted at KIST Medical College from Jan 2014 to Jan 2018. The study included ninety six prostatic specimens received in department of pathology. Hematoxylin and Eosin stained slides were retrieved and reviewed. The specimens and slides were analyzed according to type of specimen, age of patient, histopathological pattern and final diagnosis. Results were analyzed using Statistical Package for Social Science (SPSS, version 21) for Windows. Independent t test was used to correlate the mean age between patients with benign and malignant lesions. P value less than 0.05 was considered as statistically significant.Results: The most common benign lesion was nodular hyperplasia of prostate 86(89.58%). Malignant lesions comprised 8 (8.34%) cases of all prostatic lesions. All the cases of prostate carcinoma were adenocarcinoma. The most frequent Gleason score was 9. Mean age for benign and malignant lesions were 69.6 ± 8.1 years and 72.9 ± 5.2 years respectively. There was no significant difference in the mean age between patients with benign and malignant lesions (p value 0.27).Conclusion: Benign lesions of prostate are more common than malignant lesions. Histopathological examination of prostate specimens have important role in diagnosing various benign and malignant lesions, especially to rule out incidental carcinoma.JMMIHS.2018;4(1):12-19